LIPID PROFILE AND GENETIC MARKERS ASSOCIATED WITH THE LEVEL OF OXIDIzED LOW DENSITY LIPOPROTEIDES - E. Yu. Khlebus; А. N. Meshkov; V. Z. Lankin; А. A. Orlovsky; А. V. Kiseleva; N. V. Shcherbakova; А. А. Zharikova; А. I. Ershova; А. К. Tikhaze; Е. B. Yarovaya; I. Е. Chazova; S. А. Boytsov (Российский кардиологический журнал)
Aim. To assess biochemical  and  genetic  markers  associated with the  level of oxidized low density lipoproteides (oxLDL).Material and methods. Patients with various cardiovascular  risk according  to the SCORE scale were included in this study. Biochemical parameters were measured in blood serum  with automatic  analyzer Architect C8000 (Abbott, USA). OxLDL level was measured with the  hard-phase immune-enzyme  assay  Oxidized LDL  ELIsA (Mercodia, sweden). Genotyping was performed  via the Cardio-MetaboChip microarrays (Illumina, USA). Seventeen single-nucleotide polymorphisms (SNP) of the  APOB gene  were  included  into analysis:  rs676210,  rs1042034,  rs6728178, rs6754295,  rs673548,  rs6711016,  rs11902417, rs10184054, rs6544366, rs4564803, rs7557067, rs2678379, rs533617, rs679899, rs1801695, rs1367117, rs1042031.  The association  study between SNP and oxLDL level was performed by the ROC-analysis. Based  on results,  the group of SNP was selected. According to this group,  the  total SCORE  (TS) showing the  level of genetic  susceptibility to an increased oxLDL level was calculated.Results. The present study included 717 patients ranging from 28 to 84 years old (with the median of 57), 204 men (28.45%). The oxLDL level varied from 21,03 to 163,72 U/dL (median 68,5) and correlated with the levels of total cholesterol  (TC), triglycerides (TG), low density cholesterol  (LDL-C), C-reactive  protein (C-RP) and apolipoprotein B-100 (ApoB-100). The highest coefficients of correlations (p<10-10) were derived for APOB-100 and LDL-C (0,61 and 0,55, respectively). Fourteen SNPs of the APOB gene  (rs6728178,  rs11902417, rs6544366,  rs4564803,  rs6754295, rs7557067, rs1042034, rs2678379, rs676210, rs673548, rs679899, rs6711016, rs10184054, rs1042031)  were significantly associated with the oxLDL. For the ts calculation we used only ten out of fourteen SNP because of the presence of linked SNP. Patients  with ts ≤3 were referred  to as those  who had genetic  susceptibility to the increased oxLDL level due to the protective role of most sNP. The regression study has revealed that patients with the same ApoB-100 level and with ts ≤3 had higher oxLDL level in average  of 10 units than the patients with the ts>3 (p<10    ),and the patients with the same LDL-C level by 5 units, respectively (p<10  ).Conclusion. The oxLDL level depends on the level of LDL-C and ApoB-100 in blood, as well as on the genetic susceptibility — a combination of the SNP of APOB gene.